Peningkatan Keterampilan Berdiskusi dan Pemahaman Nilai-Nilai Pancasila Melalui Model Pembelajaran Berbasis Proyek Pada Siswa Kelas I MIS Tahfizh Rabbani Kota Solok - Rika Afriani, Vino; Anggraini, Rini (LPPI Yayasan Almahmudi bin Dahlan, 2025)
Civic Education in grade I at MIS Tahfizh Rabbani still faces challenges in achieving Learning Outcomes, particularly in the element of “The Unitary State of the Republic of Indonesia,” which requires understanding and practicing Pancasila values. Lecture-based methods make it difficult for students to grasp abstract values and engage in discussions. This classroom action research aimed to improve discussion skills and understanding of Pancasila values through Project-Based Learning (PjBL), conducted in two cycles with 15 first-grade students. Data were collected through observation, documentation, and project assessments. The results showed an increase in discussion participation from 20% in the pre-cycle to 60% in Cycle I, and 86.7% in Cycle II, along with the ability to connect project outcomes with Pancasila values. Thus, PjBL is effective in enhancing students’ discussion skills and understanding of Pancasila values and is recommended for other learning contexts requiring conceptual understanding and social skill development.